Digital Builders Sdn Bhd (DBSB). customer service as a competitive advantage. a study on customer’s perception towards DBSB Shell Gas Services / Hartini Abdul Halim and Zuraini Hassan - Abdul Halim, Hartini; Hassan, Zuraini (2005)
In today’s competitive marketplace, service provider like Digital Builders Sdn Bhd (DBSB) Shell Gas must provide products and services that improve their customer’ competitive performance and business results. They must exceed customer perception and expectation. To survive and grow, DBSB Shell Gas needs satisfied and loyal customers. This research is attempted to studying the customer’s perception towards DBSB Shell Gas services, to study and analyze current marketing strategy and customer service practice and to formulate new strategies and a plan of action to improve good perception towards DBSB Shell Gas. Uncontrolled Keywords: